SOCIOLOGICAL DISCOURSE IN THE QUR’AN : Human Relation from Perspective of Sociological Establishment - Solihin, Sohirin Muhammad; Jasim, Layth Suud (Universitas Islam Indonesia, 2017)
This paper attempts to study different aspects of the sociological discourse in the Qur’an. The guiding principles in the Qur’an are not confined to spiritual matters rather they are beyond the whole activities of mankind. The area of study is not to discuss it from the view point of philosophical or contemporary Islamic thought in the hands of scholars of sociology. It seems that such kind of studies, have conducted by many other researchers in that particular aspect. Our study focuses on the divine guidelines as appeared in the textual evidences in the Qur’an. On the first part, it deals with exploring the definition of Qur’anic discourse (al-khitab al-Qur’ani) which may differ from the definition given by other scholars in human sciences. It will includes various levels of discourse starting from inter individual, inter group and up to the level of political arena. Furthermore, it also focuses on the concept of community development and its main principles to come up with the outcome which, toward the end, can entertain the needs of well being which could bring them into the balance between physical and spiritual needs. In addition, it highlights the practical examples of discourses conducted by the Prophets and Messengers which could be taken as model in conducting the community development in the light of changing situation. Keywords: Qur’anic discourse, Islamic thought, sociology, and community development.